Geomorphology of the Clarion Clipperton Zone, tropical North Pacific Ocean - Parianos, John (2022)
The Clarion Clipperton Zone (CCZ) hosts a valuable deposit of polymetallic nodules. Understanding the geology of this deposit is key to its effective exploration and future mining. Interpretation of satellite derived bathymetry elucidates large scale geomorphological units and structural units that characterize the area.The Main Map is includes distinct plains, rises, and lows of abyssal hills, steps and a trough along parts of the bounding fracture zone, seamount chains, fault zones and rifts.